Guttaflow Bioseal as Monocone Obturation Technique: A Scanning Electron Microscopy Study - M, Mustaffa; N, Nordin; SNH, Embong; MS, Mohd Ibrahim (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: This study compared the obturated surface area, the extrusion of root filling material beyond the apical foramen and the duration of obturation procedure in single-rooted mandibular premolar using monocone obturation technique. MATERIALS AND METHODS: The root canal of twenty single-rooted mandibular premolars were prepared, and then divided into two groups; Group 1 (GuttaFlow Bioseal (GFB) and a gutta-percha (GP) cone) and Group 2 (RoekoSeal Automix root canal sealer and a GP cone). The obturation procedure was timed and the obturation radiograph was taken after the procedure. The roots were sectioned perpendicularly and the surfaces were observed under scanning electron microscope. The images were transferred to the SketchAndCalc Area Calculator software for evaluation of the obturated surface area. RESULTS: The median score of obturated surface area in Group 1 and 2 at the apical was 86.51 and 83.00, at the middle was 90.48 and 87.35 and at the coronal was 93.00 and 83.39, respectively. The extrusion of root filling material between two groups did not show statistically significant difference. The mean duration of obturation in Group 1 and 2 was 149.50 and 137.60, respectively. CONCLUSIONS: The obturated surface area at the apical and middle root regions in Group 1 and 2 was comparable but at the coronal region, Group 1 showed 11.5% better coverage. The extrusion of root filling material in Group 1 and 2 was equivalent. Obturation procedure in Group 1 took 8.6% longer than in the Group 2.